Resposta ao corticoesteróide inalatório em pacientes com anemia falciforme - Maynard, Kátia Cristina Amaral (2013)
Objective: To assess the therapeutic response to inhaled corticosteroids of patients with Sickle Cell Anemia (SCA). Methods: A longitudinal intervention study with children, adolescents and young adults, both genders, aged between seven and twenty-seven years old, clinically stable, without acute adverse events, with the diagnosis of SCA confirmed by hemoglobin electrophoresis. They were initially submitted to pulmonary function testing, transcutaneous oxygen saturation and peak flow. Then, they were submitted to the use of innalatory budesonide for 03 months and afterwords they were reassessed with pulmonary function testing, transcutaneous oxygen saturation and peak flow. Results: The study included 44 patients with mean age of 14.9±4,6 years, with spirometric altered profile, and 63.6% had a restrictive ventilatory disease, 22.7% obstructive and 13.6% mixed obstructive and restrictive. The measures of transcutaneous oxygen saturation, after the treatment, showed an improvement, with 43.1% of the patients with higher values than 95%, 31.8% with values between 90 to 94% and 25% values below 89%. As to the improvement of the symptoms, there was a decrease of 4.6% in the number of dyspneic, 22.7% in the number of those with cough and 2.2% in the number of those who complained of chest pain. The number of asymptomatic patients increased from 50% to 79.5%. Conclusion: The patients with obstructive and mixed obstructive and restrictive profile answered better than restrictive patients, having or not having asthma.